Digital marketing training: Empowering business actors to use digital marketing in Metro Lampung - Adha, Shultonnyck; Sutia, Sabar (Privietlab, 2025)
The era of digital transformation has changed the paradigm of human resource management in the information technology industry, where organizations that focus on human capital development through strategic training programs show performance increases of up to 75% compared to organizations that do not make similar investments. The information technology industry faces a special challenge in maintaining the relevance of employee competencies to leading technological developments, so a comprehensive evaluation of the impact of digital marketing training programs using a measurable and objective quantitative approach is needed. The purpose of this study is to analyze and measure the effectiveness of digital marketing training programs on increasing employee work productivity in Metro Lampung through a pre-post implementation comparative study approach, identifying differences in productivity levels before and after implementation, calculating the magnitude of increase, and analyzing the most responsive productivity dimensions. The study used a quantitative approach with a quasi-experimental pre-post test design on 35 IT employee respondents selected using purposive sampling technique, with data collection using a structured questionnaire on a Likert scale of 1-5 and paired sample t-test analysis. The results showed a significant increase in work productivity (p < 0.001) by 20.2% with a confidence interval of 95% (18.7%-21.7%), where the Innovation Index achieved the highest responsiveness (23.0%, Cohen's d = 2.29), followed by Task Completion Rate (20.6%), Quality Performance (19.8%), and Collaboration Effectiveness (18.0%). Digital marketing training programs have proven to be effective in increasing work productivity with 97.1% of respondents experiencing progress in at least three of the four dimensions evaluated. Organizations need to optimize resource allocation on innovative technology training modules, integrate a holistic approach that leverages synergistic effects across productivity dimensions, and implement training personalization strategies to maximize outcomes for all participants.